Inhibition of In Vitro Infection of Hepatitis B Virus by Human Breastmilk - Yuqian Luo; Kuanhui Xiang; Jingli Liu; Ji Song; Jing Feng; Chen, Jie; Yimin Dai; Yali Hu; Hui Zhuang; Yihua Zhou (Nutrients, 2022)
Despite the presence of hepatitis B virus (HBV) in the human breastmilk of mothers infected with HBV, it has been shown that breastfeeding does not increase the risk of mother-to-child transmission (MTCT) of HBV. We tested the hypothesis that human breastmilk may contain active components that bind to HBV and inhibit the infectivity of HBV. The results show that human whey significantly inhibited the binding of the hepatitis B surface antigen (HBsAg) to its antibodies in competitive inhibition immunoassays. The far-western blotting showed that HBsAg bound to a protein of 80 kD in human whey, which was identified as lactoferrin by mass spectrometry. Competitive inhibition immunoassays further demonstrated that both human lactoferrin and bovine lactoferrin bound to HBsAg. Human whey, human lactoferrin, and bovine lactoferrin each significantly inhibited the infectivity of HBV in vitro. Our results indicate that human breastmilk can bind to HBsAg and inhibit the infectivity of HBV, and the active component is lactoferrin. The findings may explain the reason that breastfeeding has no additional risk for MTCT of HBV, although human breastmilk contains HBV. Our study provides experimental evidence that HBV-infected mothers should be encouraged to breastfeed their infants.